Journalists' Views and Management of Dark Participation. Issue 2 (4th March 2023) - Al-Rawi, Ahmed; Kim, Taeyoung
ABSTRACT: This study investigates how Canadian journalists view dark participation and respond to it. Based on interviews with 15 journalists, it explores their concern about dark participation practices especially in relation to the issues of hate speech, dis/misinformation, and trolling. Combined with the ripple effects of social media in delivering news content, the respondents indicated that there are multiple challenges and concerns when dealing with dark participation such as attacks on women and different minority groups which might threaten social cohesion. The majority of respondents highlighted the psychological toll of dark participation and ways of dealing with it.